An Effective Power Dispatch Strategy for Clustered Micro-grids while Implementing Optimal Energy Management and Power Sharing Control using Power Line Communication - Ahmed Mohamed, Ahmed Haidar; Adila, Fakhar; Muttaqi, Kashem M (IEEE, 2019)
The mitigation of uncertainty in the availability of power generation from micro-grids to enable renewable resources to be dispatched is a daunting task for individual operators. Installing energy storage systems may reduce the impact of renewable energy intermittency. However, a peculiarity in energy management can be arisen, particularly, when different energy providers manage these resources. Hence, an intelligent utilization approach should be devised to maximize the benefits of using battery energy storage, since the cost of this system is the most expensive part. This paper proposes an effective power dispatch strategy for clustered micro-grids. The developed hybrid algorithm implements optimal energy management and power sharing control using binary data. Frequency shift keying (FSK) technique has been adopted for transmitting the binary signal over the power line communication (PLC). A part of the algorithm is utilized to deal with the optimal scheduling control while the other actuates the dynamic demand response based Photovoltaic (PV) power forecasting. The performance of the proposed approach has been validated using data collected from the practical network of “Bario, Sarawak”. The presented results suggest that the implementation of the proposed strategy can improve the efficiency of the overall system, causing less operating cost and fast return.